2016
DOI: 10.3109/21678421.2016.1167912
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and proximo-distal bimelic amyotrophy: Evidence of cervical flexion induced myelopathy

Abstract: This report aims at describing two new clinical phenotypes associated with classical features of cervical flexion induced myelopathy (CFIM). The description is of a prospective case series of six young males presenting with progressive bilateral proximal/proximo-distal amyotrophy of upper limbs and demonstrating the typical MRI characteristics of Hirayama disease. All underwent detailed clinical, electrophysiologcal and imaging studies. The affected muscles were shoulder girdles and arms in proximal form (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Preethish-Kumar et al showed that distal, proximal, and proximodistal bimelic amyotrophy are all myelopathies that can be induced by cervical flexion (40). Thus, the functional outcome of proximal forms is likely worse and more uncertain than that of distal forms (14,56).…”
Section: Atrophy Of the Muscles Of The Proximal Upper Extremitymentioning
confidence: 99%
“…Preethish-Kumar et al showed that distal, proximal, and proximodistal bimelic amyotrophy are all myelopathies that can be induced by cervical flexion (40). Thus, the functional outcome of proximal forms is likely worse and more uncertain than that of distal forms (14,56).…”
Section: Atrophy Of the Muscles Of The Proximal Upper Extremitymentioning
confidence: 99%
“…coined the term “Distal BiMelic Amyotrophy” (DBMA) to describe a symmetrical amyotrophy of the distal upper extremities with rapid progression to severe motor disability and showing similar MRI features with the previously described entity of MMA/HD (eg, flexion‐induced cervical myelopathy at C8‐T1 myelomers) 9 . Also, the flexion‐induced myelopathy may spread from C8‐T1 myelomeres to two segment higher or lower than MMA/HD (eg, C5‐T1 myotomes), leading to a “Proximal BiMelic Amyotrophy” (PBMA) or “Proximo‐Distal biMelic Amyotrophy” (PDMA) 10 . However, the absence of sensory, pyramidal, and cerebellar signs, as well as the presence of a cold paresis are common features of HD regardless of the type of muscular atrophy.…”
Section: Introductionmentioning
confidence: 68%
“…However, increased understanding of the disease has led to the recognition that patients could experience amyotrophy of the proximal muscles in the upper limbs. Some studies have included patients with proximal symptoms ( 9 , 17 ). Patients with proximal symptoms have been considered in the development of new diagnostic criteria and a new clinical classification system ( 1 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, strict criteria for the diagnosis of HD with proximal involvement are needed to prevent misdiagnosis and potential negative outcomes. Some criteria have been defined ( 9 , 10 ), but controlled studies and synthesis of results across studies are lacking.…”
Section: Introductionmentioning
confidence: 99%